Spodoptera frugiperda Uses Specific Volatiles to Assess Maize Development for Optimal Offspring Survival - Hanbing Li; Peng Wan; Zhihui Zhu; Dong Xu; Shengbo Cong; Min Xu; Haichen Yin (Insects)
Spodoptera frugiperda, a major global agricultural pest, poses significant challenges to chemical control methods due to pesticide resistance and environmental concerns, underscoring the need for sustainable management strategies. Attractants based on host plant volatiles offer a promising eco-friendly approach, but their development for S. frugiperda is hindered by limited research on host recognition mechanisms. This study reveals that female S. frugiperda preferentially oviposit on maize at the seedling stage. Using electrophysiological techniques, we identified p-xylene and (+)-camphor from seedling-stage maize volatiles as key compounds eliciting strong responses in female S. frugiperda. Behavioral assays confirmed that these compounds (p-xylene at the concentration of 5%, 10%, and 20% and (+)-camphor at 1%, 5%, and 10%) significantly attract females, establishing them as the key odor cues for host selection. Moreover, these volatiles are more abundant in seedling-stage maize, suggesting that S. frugiperda assesses maize growth stages based on their concentrations. Importantly, larvae reared on seedling-stage maize exhibited higher survival rates than those on later-stage maize, indicating that oviposition site selection directly affects offspring fitness. These findings demonstrate that S. frugiperda uses p-xylene and (+)-camphor to evaluate maize development and select suitable oviposition sites, thereby enhancing larval survival. This study provides a foundation for developing targeted attractants for S. frugiperda and highlights the seedling stage as a critical period for implementing pest control measures, particularly in autumn maize production, given the higher pest population density during this phase.